Glass transition temperature: Basics and application in pharmaceutical sector - Jadhav, Namdeo R; Gaikwad, Vinod L; Nair, Karthik J; Kadam, Hanmantrao M (Asian Journal of Pharmaceutics (AJP), 2014)
Glass transition temperature (Tg) is an important tool used to modify physical properties of drug and polymer molecules. g is shown by certain crystalline as well as amorphous solids. During the process of heating, some solid gets melted and if quench cooled, instead of crystallizing, gets converted to amorphous solid form appearing as that of glass. This glass formation is seen because of the dynamic arrest of molecules forming a disordered state at Tg. The molecules/atoms in glassy state are subject to only vibration and not translational and rotational motion. Mainly, at Tg, conversion of glassy (vitrified, amorphous) solid to rubbery (viscous liquid) takes place. Numerous factors like structural change in molecules, cooling rate and incorporation of additives alter the Tg. Techniques like differential scanning calorimetry, elastic modulus, broad-line NMR are used to measure the Tg of substances. The change in Tg has been carried out to improve dissolution and bioavailability, processing and handling qualities of the material.